Neuroanatomic and neurocognitive phenotype in Williams syndrome - Sampaio, Adriana; Osorio, Ana; Fernández, Montse; Carracedo, Ángel; Garayzábal, Elena; Fernandes, Catarina; Vasconcelos, Cristiana; Gonçalves, Óscar F. (Revista de Investigación en Logopedia, 2013)
Williams syndrome (WS) is a neurodevelopmental genetic disorder characterized by a dissociation in their cognitive architecture, in which severe visuospatial cognition deficits contrast with relatively preserved language, face recognition, and short-term auditory skills. This cognitive dissociation has also been proposed to characterize their brain structure. In this study, we analysed the structural and neurocognitive phenotype in WS and typically developing groups. Therefore, we analysed the relationship between brain white matter, grey matter and regions of interest (superior temporal gyrus and hippocampus) with neurocognitive functioning. The results of this study showed differences between with respect to the type of correlations observed for WS and typically developing groups. These differences in the pattern of association between cognitive and brain measures suggest altered neurodevelopmental patterns in WS.